Form of Communication for Teaching Bajo Children The Local Values in Utilizing Natural Marine Resources - Jumaidin, La Ode; Irawati, Irawati; Udu, Sumiman; Hasddin, Hasddin; Husen, Osu Oheoputra (UIN Maulana Malik Ibrahim Malang, 2024)
The issue behind the research on the Bajo tribe is the lack of understanding regarding the forms of communication used by the tribe to impart knowledge about local wisdom concerning the sustainable use of coastal and marine resources. Therefore, the aim of this research is to identify both the forms of local wisdom and the communication methods used to educate Bajo children about the sustainable use of coastal resources, ensuring the preservation of the Bajo tribe's cultural identity. The study was conducted among the Bajo tribe living along the coast of the Tiworo Strait in Muna Regency and West Muna Regency. The research informants consisted of 15 individuals, purposively selected, including elders and tribal leaders. The findings revealed that the local wisdom being passed down includes traditional management of coastal natural resources, such as: (a) the mammia kadialo tradition, involving fishing practices, which include palilibu, pongka, and sasakai; (b) traditional methods of fishing, including missi, ngarua, mana (archery using traditional tools), and nyuluh/balobe (also called ngobor); (c) the Pamali tradition, which involves specific taboos at certain times and places; and (d) the Maduai Pinah ritual, a form of worship for the